Multi-criteria optimization in CO2 laser ablation of multimode polymer waveguides. (December 2015) - Tamrin, K.F.; Zakariyah, S.S.; Sheikh, N.A.
Abstract: High interconnection density associated with current electronics products poses certain challenges in designing circuit boards. Methods, including laser-assisted microvia drilling and surface mount technologies for example, are being used to minimize the impacts of the problems. However, the bottleneck is significantly pronounced at bit data rates above 10 Gbit/s where losses, especially those due to crosstalk, become high. One solution is optical interconnections (OI) based on polymer waveguides. Laser ablation of the optical waveguides is viewed as a very compatible technique with ultraviolet laser sources, such as excimer and UV Nd:YAG lasers, being used due to their photochemical nature and minimal thermal effect when they interact with optical materials. In this paper, the authors demonstrate the application of grey relational analysis to determine the optimized processing parameters concerning fabrication of multimode optical polymer waveguides by using infra-red 10.6 µm CO2 laser micromachining to etch acrylate-based photopolymer (Truemode ™ ). CO2 laser micromachining offers a low cost and high speed fabrication route needed for high volume productions as the wavelength of CO2 lasers can couple well with a variety of polymer substrates. Based on the highest grey relational grade, the optimized processing parameters are determined at laser power of 3 W and scanning speed of 100 mm/s. Highlights: CO2 laser ablation of optical polymer waveguides was considered. A three-dimensional surface fitting was used in the unstructured experimental data. Insertion loss was non-linearly correlated with the depth of ablation and track width. Ablation quality characteristics were determined using grey relational analysis. Optimal ablation was achieved at low power (3 W) and low scanning speed (100 mm/s).